Legal Review of the Problems of Registering Creations as Written Documents of Copyright Ownership at the DJKI, Ministry of Law in Indonesia - Putri Rahmawati; Anis Mashdurohatun (UNISSULA Semarang, 2025)
Abstract. This study examines in depth the mechanism of registering works as written documents of copyright ownership in Indonesia, as well as the accompanying problems, focusing on the dualism between the principle of automatic and declarative copyright protection as stipulated in Law No. 28 of 2014 concerning Copyright, and the existence of a registration mechanism organized by DJKI. The background of this research problem is driven by the importance of intellectual property rights as a manifestation of human intellectual abilities that are protected by law, abolished in the theory of natural rights and utilitarianism, as well as its constitutionality in Article 28D paragraph (1) of the 1945 Constitution of the Republic of Indonesia. Although copyrights appear automatically, the registration of works has a crucial function as an initial proof of ownership, which is later strengthened by the development of the E-Copyright system. However, this bold ease of access opens up the potential risk of data manipulation and overlapping claims, exacerbated by digital literacy challenges among creators. The purpose of this study is to analyze the effectiveness of the creation registration system in providing definite, fair, and beneficial protection for creators, as well as to identify the juridical and non-juridical content of this dynamic, including its relevance to the case of